2009
DOI: 10.1152/ajpgi.00261.2009
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate maldigestion induces necrotizing enterocolitis in preterm pigs

Abstract: Necrotizing enterocolitis (NEC) remains the most severe gastrointestinal disorder in preterm infants. It is associated with the initiation of enteral nutrition and may be related to immature carbohydrate digestive capacity. We tested the hypothesis that a formula containing maltodextrin vs. a formula containing lactose as the principal source of carbohydrate would predispose preterm pigs to a higher NEC incidence. Cesarean-derived preterm pigs were given total parenteral nutrition for 48 h followed by total en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
126
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 112 publications
(135 citation statements)
references
References 52 publications
(66 reference statements)
6
126
1
Order By: Relevance
“…associated with increases in key functions such as digestive enzyme activity, nutrient absorption, and immunological tolerance to bacterial colonization (27,(33)(34)(35). Our follow-up studies show that the difference in intestinal mass per body weight between preterm and term pigs on day 5 disappears over the following weeks but that the general deficits in body growth and many behavioral characteristics (regardless of diet during the first 5 d) remain until at least 4 wk of age (36).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…associated with increases in key functions such as digestive enzyme activity, nutrient absorption, and immunological tolerance to bacterial colonization (27,(33)(34)(35). Our follow-up studies show that the difference in intestinal mass per body weight between preterm and term pigs on day 5 disappears over the following weeks but that the general deficits in body growth and many behavioral characteristics (regardless of diet during the first 5 d) remain until at least 4 wk of age (36).…”
Section: Discussionmentioning
confidence: 59%
“…Colostrum contains high concentrations of trophic and immunoregulatory factors (24) and a rapid progression of enteral feeding with BC or porcine colostrum (120 ml/ kg/d from day 3 after birth) results in less NEC in preterm pigs, relative to IF (25,26). It is noteworthy in this study that IF remained inferior to BC and HM, even using a relatively slow (27). Furthermore, IF products are clearly inferior to intact milk products in stimulating immunity and mucosal defense mechanisms (28)(29)(30).…”
Section: Discussionmentioning
confidence: 71%
“…16 Additionally, MDX consumption by preterm piglets lead to the expansion of ileal E. coli populations 17 and induced necrotizing enterocolitis in these animals, but not in fully developed pigs. 18 Increased levels of E. coli and AIEC strains have been repeatedly observed in ileal CD patients, suggesting a role for E. coli in disease pathogenesis. [19][20][21] In earlier work from our laboratory, we found that patients with ileal CD have a mucosal microbiome enriched for MDX metabolism, as compared to colonic CD patients and non-IBD controls.…”
Section: Maltodextrin (Mdx) Is a Common Food Additive That Alters Botmentioning
confidence: 99%
“…Notable studies have demonstrated a direct effect of these compounds on mucosal barrier integrity, which translates to exacerbated intestinal inflammation or increased bacterial burdens in animal models. 17,18,27 Likewise, restrictive diets that eliminate processed foods are showing clinical Figure 3. Consumption of MDX decreases the mucosal barrier of the intestine and increases the proximity of commensal bacteria to the epithelial layer.…”
Section: Cultivating a Greater Understanding Of The Effect Of Diet Onmentioning
confidence: 99%
“…This inconsistency might be related to the digestibility of nutrients for the premature pig. It has been reported that the less-digestible maltodextrin-based formula induced higher incidences of necrotizing enterocolitis compared with the highly digestible lactose-based formula in preterm pigs (Thymann et al, 2009). This raises the question of how the composition of the formula could impact the intestinal development of IUGR neonates.…”
Section: Discussionmentioning
confidence: 99%